GROUP WORK AT A FOREIGN LANGUAGE LESSON - Olena Y. Beresten; Oleksandr O. Pliushchai (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология, 2021)
The article is devoted to the topic of group work in a foreign language lesson. Before proceeding to the methodological developments, the authors focused on the analysis of domestic researchers’ publications on this issue. This list includes such authors as M. Bytyanova, Yu.V. Buzova, S.G. Dobrynina, L.A. Kozakova, O. Kondratyuk, O.V. Chikhanova, T.L. Shepelenko. The authors of the article agree with the researcher L.A. Kozakova who states that pair and group work significantly increase the volume and duration of foreign language speech, because students speak at the same time. Indeed, with a large number of students, it is very important to give each student an opportunity to participate in all kinds of work in the classroom. It is group work that enhances the language acquisition process. According to the researcher O. Kondratyuk, only the joint work of the group should be evaluated, without giving students who worked together different grades. The teacher should write down the mistakes of students and then, after listing the good aspects of group work, focus on the main mistakes. The researcher Bytyanova considered the principles of grouping. She emphasizes that only with the correct selection of groups, students begin to respect the opinion of a classmate, cultivate tolerance and tact. The scientist S.G. Dobrynina says that group work is suitable for tasks that require a great amount of work, a variety of knowledge and skills, develop creative thinking, their content is interesting and informative, the level of complexity is average or higher than average. Thus, the authors of the article have developed a number of tasks designed for students learning German at the A2 level. The purpose of these tasks is to revise the grammar learnt at the A1 level and to introduce new vocabulary. The authors offer the first task to meet new members of the group. The originality of the task is to use music as a time limit. The next task developed by the authors is a game of hide-and-seek: one group hides various objects in the class and the other looks for them, training the grammatical material, local prepositions in this case. The next game “quartet” can be adapted to any lexical material, but the authors have devoted it to kitchen utensils. Finally, the authors developed a step-by-step work on the text, which includes frontal, group and individual work. The authors made the following conclusions: group work contributes to students’ collaboration; adds mobility to the lesson; students constantly communicate with each other in the form of a dialogue; passive students are actively involved in work; group work diversifies the learning process.